Damage assessment of carbon-epoxy composites with and without resin flow channels. (1st March 2019) - Karumbaiah, Kariappa M.; Kracke, Christoph; Battley, Mark; Bickerton, Simon; Allen, Tom
Abstract: The integration of resin flow channels in resin transfer moulding aids manufacturers in numerous ways. They reduce total flow resistance, allowing faster filling, and provide the capability to steer resin flow within a mould. However, the presence of resin flow channels in moulded composites results in local geometric variations affecting fibre alignment. In this work, the static tension and flexural performance of composite laminates with resin flow channel(s) have been investigated. Acoustic emission monitoring was used to characterise damage. The frequency of each distinct damage event was monitored to categorise the damage. Under flexural loads, multiple channel specimens demonstrated damage initiation at lower loads and a high accumulation of AE based damage events when channels were facing the compression side of the bending loads. This study provides insight to the damage mechanism of composites with and without resin flow channels.